The relationship of adverse childhood experiences to a history of premature death of family members - Valerie Edwards J; Perry Geraldine S; Giles Wayne H; Felitti Vincent J; Brown David W; Dong Maxia; Anda Robert F; Dube Shanta R (BMC, 2009)
Abstract Background To assess the association between adverse childhood experiences (ACEs), including childhood abuse and neglect, and serious household dysfunction, and premature death of a family member. Because ACEs increase the risk for many of the leading causes of death in adults and tend to be familial and intergenerational, we hypothesized that persons who report having more ACEs would be more likely to have family members at risk of premature death. Methods We used data from 17,337 adult health plan members who completed a survey about 10 types of ACEs and whether a family member died before age 65. The prevalence of family member premature death and its association with ACEs were assessed. Results Family members of respondents who experienced any type of ACEs were more likely to have elevated prevalence for premature death relative to those of respondents without such experience (p < 0.01). The highest risk occurred among those who reported having been physically neglected and living with substance abusing or criminal family members during childhood. A powerful graded relationship between the number of ACEs and premature mortality in the family was observed for all age groups, and comparison between groups reporting 0 ACE and ≥ 4 ACEs yielded an OR of 1.8 (95%CI, 1.6-2.0). Conclusion Adverse childhood experiences may be an indicator of a chaotic family environment that results in an increased risk of premature death among family members.